Boehmiella wilsoni (Nematoda, Heligmosomoidea, Boehmiellidae fam. nov.), found in Amazonian rodents. (December 2020) - Andrade-Silva, B.E.; Vilela, R.V.; Lopes-Torres, E.J.; Costa-Neto, S.F.; Maldonado, A.
Abstract: The genus Boehmiella was initially described as a member of the family Trichostrongylidae. Subsequently, it was assigned to the subfamily Haemonchinae in the family Haemonchidae. We analyzed parasites of spiny tree-rats, Mesomys hispidus, collected in the Amazon rainforest, which were identified as B. wilsoni based on integrative taxonomy. Using morphology, morphometry, and scanning electron microscopy (SEM), we added new data to the original description of the species. We also inferred phylogenetic hypotheses for its relationships within the Trichostrongylina, based on partial nuclear 18S and 28S rRNA genes, through Maximum Likelihood and Bayesian analyses. In conclusion, B. wilsoni does not belong to the family Haemonchidae, nor is it closely related to any other trichostrongylin family, and therefore, we propose the establishment of a new family, Boehmiellidae fam. nov., to which the genus Boehmiella is allocated. Graphical abstract: Image 1 Highlights: Helminth found in arboreal rodent of the Amazon region, with description of new host, new geographical distribution, new taxonomic data, and proposal of a new family to allocate the genus according to molecular and morphological analyses.